2017
DOI: 10.1007/s40858-017-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

A weather-based model for predicting early season inoculum build-up and spike infection by the wheat blast pathogen

Abstract: Wheat blast, caused by the fungus Magnaporthe oryzae Triticum pathotype (MoT), is a serious disease capable of causing severe losses, especially during warm and humid weather conditions. Although the pathogen attacks all aboveground parts, infection of the wheat spikes is of major concern. In this work we developed and evaluated a prediction model based on the analysis of historical epidemics and weather series in the northern Paraná state, Brazil (Apucarana, Maringá and Londrina) and available epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 23 publications
(25 reference statements)
4
27
0
1
Order By: Relevance
“…The optimum weather conditions for wheat blast development include long and frequent periods of leaf wetness (24–40 h), coupled with high temperatures (25–30 °C) (Cardoso et al ., ). In Brazil, a predictive model for wheat blast outbreaks based on daily climatic data, named Sisalert ( Plant Disease Epidemic Risk Prediction System ), was developed to calculate the risk of an epidemic (available at: https://dev.sisalert.com.br/monitoramento/?page_id=14; Fernandes et al ., ; Nicolau et al ., ). In the USA, a climatic model adapted from this Brazilian model indicated that the weather conditions were favourable to wheat blast in 25% of the winter wheat cropping regions, with suitable conditions for wheat blast outbreaks in 70% of the years for Louisiana, Mississippi and Florida (Cruz et al ., ).…”
Section: Strategies For the Management Of Wheat Blastmentioning
confidence: 98%
“…The optimum weather conditions for wheat blast development include long and frequent periods of leaf wetness (24–40 h), coupled with high temperatures (25–30 °C) (Cardoso et al ., ). In Brazil, a predictive model for wheat blast outbreaks based on daily climatic data, named Sisalert ( Plant Disease Epidemic Risk Prediction System ), was developed to calculate the risk of an epidemic (available at: https://dev.sisalert.com.br/monitoramento/?page_id=14; Fernandes et al ., ; Nicolau et al ., ). In the USA, a climatic model adapted from this Brazilian model indicated that the weather conditions were favourable to wheat blast in 25% of the winter wheat cropping regions, with suitable conditions for wheat blast outbreaks in 70% of the years for Louisiana, Mississippi and Florida (Cruz et al ., ).…”
Section: Strategies For the Management Of Wheat Blastmentioning
confidence: 98%
“…Several prediction models were proposed for wheat blast ( Cardoso et al, 2008 ; Fernandes et al, 2017 ). The models used climate data such as temperature, relative humidity, rainfall, and solar radiation, and calculated values contributing to development of wheat blast (inoculum potential, spore cloud, and day favouring infection (DFI)).…”
mentioning
confidence: 99%
“…Xu (2003) working with disease forecasting system for FHB, reported that the models include the effects of weather variables on two aspects of epidemic development: i) spore production, which requires sufficient rainfall about 8─10 days prior to and during anthesis, to improve production of ascospore and conidia; ii) spore dispersal and infection, which demand enough rainfall to disperse ascospores and/or conidia, followed by prolonged periods of warm humid conditions that are conducive for infection of spikes. On the other hand, Fernandes et al (2017) reported in their study about weather-based model for predicting WB inoculum and infection that persistent rainy and warm conditions may warrant pathogen survival during spring and summer seasons in the form of conidia and mycelia on seed, wheat volunteers, plant debris, grass weed and cultivated species. Thus, the WB infection-based models have to include a combination of weather events at both, pre-and within-season, which affect inoculum build-up, spread and infection.…”
Section: Discussionmentioning
confidence: 99%